Report of High-Risk Carbapenem-Resistant K. pneumoniae ST307 Clone Producing KPC-2, SHV-106, CTX-M-15, and VEB-1 in Greece - Maria Chatzidimitriou; Pandora Tsolakidou; Maria Anna Kyriazidi; Sotiris Varlamis; Ilias S. Frydas; Maria Mavridou; Stella Mitka (Antibiotics)
Background/Objectives: Klebsiella pneumoniae ST307 is emerging as a significant global high-risk antimicrobial-resistant (AMR) clone with a notable capacity to acquire and disseminate resistance genes. However, there is limited research on the pathogenicity, virulence, and adaptation of ST307 strains and on the clinical characteristics of infected patients. Methods: In this study, a carbapenem-resistant K. pneumoniae (CRKP) ST307 strain named U989 was isolated from a urine culture of a hospitalized patient in Volos, Greece, in July 2024. Whole-genome sequencing was performed to identify resistance genes to β-lactams blaKPC-2, blaCTX-M-15, blaTEM-1B, blaOXA-1, blaOXA-10, blaSHV-106, and blaVEB-1 and resistance genes to other antibiotics. Results: A genomic analysis also revealed the presence of virulence factors such as iutA, clpK1, fyuA, fimH, mrkA, Irp2, and TraT and an IncFiB(pQil)/IncFII(K) replicon, which harbors the blaKPC-2 gene. Additionally, the transposable element Tn4401 was identified as a key vehicle for the mobilization of the blaKPC-2 resistance gene. Finally, this is the report of a high-risk CRKP ST307 clone expressing KPC-2, SHV-106, CTX-M-15, and VEB-1 bla genes in Greece. Conclusions: The coexistence of these resistance genes in addition to aminoglycoside, quinolone, and other resistance genes results in difficult-to-treat infections caused by respective carrier strains, often requiring the use of last-resort antibiotics and contributing to the global challenge of antimicrobial resistance.